Automatic limit and shakedown analysis of 3-D steel frames - Hung, Nguyen Dang; Long, Hoang Van (Vietnam Journal of Mechanics, 2007)
This paper presents an efficient algorithm for both limit and shakedown analysis of 3-D steel frames by kinematical method using linear programming technique. Several features in the application of linear programming for rigid-plastic analysis of three-dimensional steel frames are discussed, as: change of the variables, automatic choice of the initial basic matrix for the simplex algorithm, direct calculation of the dual variables by primal-dual technique. Some numerical examples are presented to demonstrate the robustness, efficiency of the proposed technique and computer program.